Are We Winning or Losing the Battle With Periprosthetic Joint Infection: Trends in Periprosthetic Joint Infection and Mortality Risk for the Medicare Population - Kurtz, Steven M.; Lau, Edmund C.; Son, Min-Sun; Chang, Ellen T.; Zimmerli, Werner; Parvizi, Javad (The Journal of arthroplasty, 2018)
Periprosthetic joint infection (PJI) is a potentially deadly complication of total joint arthroplasty. This study was designed to address how the incidence of PJI and outcome of treatment, including mortality, are changing in the population over time. Primary total hip arthroplasty (THA) and total knee arthroplasty (TKA) patients with PJI from the 100% Medicare inpatient data set (2005-2015) were identified. Cox proportional hazards regression models for risk of PJI after THA/TKA (accounting for competing risks) or risk of all-cause mortality after PJI were adjusted for patient and clinical factors, with year included as a covariate to test for time trends. The unadjusted 1-year and 5-year risk of PJI was 0.69% and 1.09% for THA and 0.74% and 1.38% for TKA, respectively. After adjustment, PJI risk did not change significantly by year for THA (P = .63) or TKA (P = .96). The unadjusted 1-year and 5-year overall survival after PJI diagnosis was 88.7% and 67.2% for THA and 91.7% and 71.7% for TKA, respectively. After adjustment, the risk of mortality after PJI decreased significantly by year for THA (hazard ratio = 0.97; P < .001) and TKA (hazard ratio = 0.97; P < .001). Despite recent clinical focus on preventing PJI, we are unable to detect substantial decline in the risk of PJI over time, although mortality after PJI has declined. Because PJI risk appears not to be changing over time, the incidence of PJI is anticipated to scale up proportionately with the demand for THA and TKA, which is projected to increase substantially in the coming decade.